2020
DOI: 10.1002/jimd.12335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interventional and non‐interventional variables on anthropometric long‐term development in glutaric aciduria type 1: A national prospective multi‐centre study

Abstract: Glutaric aciduria type 1 (GA1) is a rare neurometabolic disorder, caused by inherited deficiency of glutaryl‐CoA dehydrogenase, mostly affecting the brain. Early identification by newborn screening (NBS) significantly improves neurologic outcome. It has remained unclear whether recommended therapy, particular low lysine diet, is safe or negatively affects anthropometric long‐term outcome. This national prospective, observational, multi‐centre study included 79 patients identified by NBS and investigated effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…Lately, malignant brain tumours have been reported in three HE patients not receiving recommended therapy 27 . A recent study also reported on larger head circumferences in HE compared to LE patients 25 . In fact, the clinical impact of these observations is still unknown.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Lately, malignant brain tumours have been reported in three HE patients not receiving recommended therapy 27 . A recent study also reported on larger head circumferences in HE compared to LE patients 25 . In fact, the clinical impact of these observations is still unknown.…”
Section: Discussionmentioning
confidence: 83%
“…The phenotypic spectrum was extended by insidious-onset dystonia, which is still observed in screened individuals not adhering to or not receiving recommended MT 1,10 . Anthropometric and MRI studies elucidated phenotypic differences between the two biochemical phenotypes; HE individuals more often than LE individuals developed macrocephaly and progressive white matter abnormalities with unclear clinical relevance 24,25 . Recently, chronic kidney dysfunction, which was not impacted by recommended therapy or the neurologic phenotype, was identified as a first non-neurologic disease manifestation 1,4 , and malignant brain tumours and audiological manifestations were described in single patients 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the first guideline mostly included grade D and a few grade C recommendations, reflecting significant uncertainty (59), the level of evidence and grade of recommendations have been improved continuously, demonstrated by the first (60) and second revision (61). This progress was much accelerated by careful long-term follow-up of national and international cohorts (38,56,57,59,(61)(62)(63)(64)(65)(66)(67)(68)(69), demonstrating that (i) newborn screening is the prerequisite of favorable neurological outcome and survival and (ii) is highly cost-effective, and that (iii) adherence to recommended maintenance and emergency treatment is associated with the most favorable neurological outcome and (iv) normal growth. Furthermore, these studies described a so far unknown renal disease manifestation, unraveled similarities (risk of striatal necrosis with concomitant complex movement disorder with predominant dystonia) and discrepancies (cognitive function, white matter changes, subdural hematoma) between biochemically delineated subgroups (high versus low excreter phenotype), and evaluated which part of the complex clinical spectrum can be specifically targeted and changed by current therapy, highlighting the need for safer and more effective medicines.…”
Section: Guideline Developmentmentioning
confidence: 99%